Can Destination-Based Cash Flow Taxes Arise in Equilibrium? - Thomas A. Gresik; Eric Bond (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We examine the effects of unilateral changes in a country's tax parameters in a two country model when both countries are part of a destination-based cash flow taxation (DBCFT) system. We con-sider deviations from a globally efficient DBCFT equilibrium by allowing each country to vary its corporate tax rate, degree of taxation of capital income, and level of border adjustment. We decompose the effect of policy changes into fiscal effects and price effects, and show that regardless of the similarity between the two countries, at least one country has an incentive to move toward taxation of capital income. If countries are identical, each has an incentive to move toward source-based taxation. In contrast, changes in corporate tax rates have neither fiscal or price effects, and thus can be set unilaterally. Our results show that an international agreement to establish multilateral DBCFT requires a commitment mechanism to prevent deviations from cash flow taxation and full border adjustments.
Keywords: H73; H21; F23; 330; destination-based taxes; source-based taxes; cash-flow taxes